CRAN-40. A NATIONAL UK GUIDELINE FOR MANAGING PITUITARY ADENOMAS IN CHILDREN AND YOUNG PEOPLE UNDER 19 YEARS DEVELOPED ACCORDING TO THE AGREE II FRAMEWORK. Issue 2 (22nd June 2018) - Blair, Jo; Korbonits, Márta; Ronaldson, Amy; Dang, Mary; Spoudeas, Helen
Abstract: Pituitary adenomas are usually benign tumours arising from the hormone-secreting cells of the anterior pituitary gland, resulting in excess hormone secretion and the development of characteristic syndromes, such as Cushing's disease, acromegaly and hyperprolactinaemia, and/or mass effects on surrounding vital structures causing for example visual disturbances and pituitary hormone deficiencies. In children and young people under 19 years (CYP), the management of pituitary adenomas is particularly challenging given their extreme rarity, more aggressive phenotype and likely genetic predisposition, as well as the lack of age- and pituitary-specific multidisciplinary teams in current decision-making and service provision. Hence, the UK sought to create national, high-quality, multi-professional guidance using AGREE II methodology under the auspices of the UK paediatric endocrine (BSPED), paediatric oncology (CCLG) and paediatric (RCPCH) societies. Twenty geographically diverse experts in adult and paediatric endocrinology, neuroradiology, clinical oncology, neurosurgery, paediatric neuropathology, and neuro-ophthalmology constituted the guideline development group and formulated 155 clinical questions. Following a systematic literature review of 409 identified papers dating from 1990 to 2016, the group made 56 evidence-based recommendations for biochemical, radiological, cytological, genetic, and ophthalmic assessment of suspected pituitary adenomas as well as surgical and oncological treatment, and follow-up. A further 55 recommendations were made based on group expert opinion and were reviewed by two rounds of an international Delphi expert consensus process. This guideline should facilitate improved clinical care and outcomes in CYP with pituitary adenomas.